An “All Teach, All Learn” Approach to Research Capacity Strengthening in Indigenous Primary Health Care Continuous Quality Improvement - McPhail-Bell, Karen; Matthews, Veronica; Bainbridge, Roxanne; Redman-MacLaren, Michelle Louise; Askew, Deborah; Ramanathan, Shanthi; Bailie, Jodie; Bailie, Ross, On Behalf of the Centre RCS Lead Group; Matthews, Veronica; McPhail-Bell, Karen; Copley, Kerry; et al. (Frontiers in Public Health, 2018)
In Australia, Indigenous people experience poor access to healthcare and the highest rates of morbidity and mortality of any population group. Despite modest improvements in recent years, concerns remains that Indigenous people have been over-researched without corresponding health improvements. Embedding Indigenous leadership, participation and priorities in health research is an essential strategy for meaningful change for Indigenous people. To centralize Indigenous perspectives in research processes, a transformative shift away from traditional approaches that have benefited researchers and non-Indigenous agendas is required. This shift must involve concomitant strengthening of the research capacity of Indigenous and non-Indigenous researchers and research translators – all must teach and all must learn. However, there is limited evidence about how to strengthen systems and stakeholder capacity to participate in and lead CQI research in Indigenous primary healthcare, to the benefit of Indigenous people. This paper describes the collaborative development of, and principles underpinning a research capacity strengthening model in a national Indigenous primary healthcare continuous quality improvement research network. The development process identified the need to address power imbalances, cultural contexts, relationships, systems requirements and existing knowledge, skills and experience of all parties. Taking a strengths-based perspective, we harnessed existing knowledge, skills and experiences; hence our emphasis on capacity ‘strengthening’. New insights are provided into the complex processes of research capacity strengthening within the context of continuous quality improvement in Indigenous primary healthcare.